(untitled) (Journal of Business Management and Accounting, 2022)
The work performance of individual employees plays an important role in increasing the labour productivity of a nation in the long term. Past studies have revealed models of work performance factors. However, the human performance system model offers a relatively more detailed and comprehensive range of determinants of individual work performance which is seemingly absent from past studies. The model’s six work performance determinants are performance specification, task support, consequences, feedback, skills/knowledge and individual capacity. A questionnaire was designed to identify research variables from each work performance determinant in the model. A pilot study was conducted to finalise it. The seven factors in our study are: competency, self-efficacy, career awareness and interests, resources and support, incentives and rewards, performance targets, and performance feedback. Data were obtained based on stratified random sampling of 4,000 employees from different job levels in the Information Technology and Network Division of a telecommunication company which yielded 3,529 final responses. The results show that out of these seven factors, performance feedback was not significant and that only the incentives and rewards factor is negatively significant with work performance. Thus, it is important for the organisation to focus on competency, self-efficacy, career awareness and interests, resources and support, and performance targets to increase labour productivity; and at the same time, carefully look into the dimensions of incentives and rewards for the benefit of a nation.